EFISIENSI PERTUMBUHAN RUMPUT LAUT Caulerpa sp. DENGAN PERBEDAAN JARAK TANAM DI TAMBAK CAGE CULTURE - Firman Ardiansyah; Hadi Pranggono; Benny Diah Madusari (LPPM Universitas Pekalongan, 2020)
The objectives of this study are to understand the effect of planting space towardsCaulerpa spseaweedgrowth, and to understand the best planting space towards Caulerpa sp seaweed growth. This research did on October until December 2018 in thefishpond of Brackish and Sea Aquaculture Laboratory PekalonganUniversity. This research used complete randomized design (CRD) which consists of three treatment and three repetition. The treatment that applied are 15 cm, 30 cm, and 45 cm of planting space. The Parameter that observed was an absolute weight growth, and water quality. Based on the result of the research showed that the highest absolute weight growth obtained on the treatment of 30 cm planting space that is 73,23gr, followed bythetreatment of 45 cm planting space that is 58,37 gr, and the last, the treatment of 15 cm planting space that is 52,43 gr. The water quality of maintenance media are, salinity ranges from 25-30 ppt, temperature ranges 29-31oC, DO ranges from 3-6, 7 mg/L, PH ranges from (6-8,5), and the brightness is 30 cm. The quality of water during research is good enough to support Caulerpa spseaweed growth.